2019
DOI: 10.3389/fpsyg.2019.01207
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Non-directive Resonance Breathing as a Treatment for Chronic Widespread Pain

Abstract: Chronic widespread pain (CWP) is one of the most difficult pain conditions to treat due to an unknown etiology and a lack of innovative treatment design and effectiveness. Based upon preliminary findings within the fields of motivational psychology, integrative neuroscience, diaphragmatic breathing, and vagal nerve stimulation, we propose a new treatment intervention, motivational non-directive (ND) resonance breathing, as a means of reducing pain and suffering in patients with CWP. Motivational ND resonance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 219 publications
0
22
0
Order By: Relevance
“…MNRB™ is a meditation-based deep breathing intervention developed by the lead author (CEP) [39] which is based on emergent ndings in integrative neuroscience and autonomic self-regulation in cardiopulmonology.…”
Section: Description Of Intervention Arms 1 Motivational Nondirectivmentioning
confidence: 99%
See 1 more Smart Citation
“…MNRB™ is a meditation-based deep breathing intervention developed by the lead author (CEP) [39] which is based on emergent ndings in integrative neuroscience and autonomic self-regulation in cardiopulmonology.…”
Section: Description Of Intervention Arms 1 Motivational Nondirectivmentioning
confidence: 99%
“…Attention is neither directed toward staying with the respiration sound guides nor directed toward observing the spontaneous ow of thoughts and sensations [44]. Sensations, such as pain, during MNRB™ are accepted without actively directing attention toward them or away from them [39].…”
Section: Description Of Intervention Arms 1 Motivational Nondirectivmentioning
confidence: 99%
“…Opioids fail to alleviate pain intensity and function [ 4 ] and cause a myriad of adverse side-effects [ 5 ] while complementary and alternative treatments have only weak to moderate effect sizes for treating CWP [ 6 ]. However, vagal nerve innervation may provide us with innovative and successful opportunities to target the complex psychophysiological framework of FM [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary intervention trials on humans [ 10 , 11 ] have shown that vagus nerve stimulation (VNS) can modulate multiple pathophysiological mechanisms inherent in various CWP conditions such as FM: VNS has shown to strongly reduce peripheral inflammatory cytokines [ 12 ] decrease sympathetic tone [ 13 ], decrease oxidative stress [ 14 ], and reverse pain-related brain activity patterns [ 7 , 15 ]. To date, VNS has been traditionally administered through invasive procedures, known as invasive VNS (iVNS), which typically involves the surgical implantation of electrodes around the vagus nerve [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation